THE INFLUENCE OF MODERN TECHNOLOGIES ON THE FITNESS INDUSTRY (Physical Culture and Sport: Scientific Perspective, 2023)
In the modern technological world, information technologies are becoming an integral part of people's everyday life; they are transforming the way we communicate, work and, importantly, take care of our health. The latest fitness technologies with a health and recreational orientation are a natural consequence of the search for effective ways to provide organized physical activity for health improvement that is accessible to the general population. The rapid development of computer and information technologies affects health and fitness services. An explosion of apps, wearable devices and digital equipment allows people to track their performance, weight and fitness level. The purpose of the research is to determine the current trends in the introduction of information technologies in the fitness industry.Analysis of publications and data related to modern technologies in the field of fitness showed that life is becoming more and more technological. The obtained results show that the general trends persist, but the impact of the COVID-19 pandemic on the state of the health and fitness industry is decreasing. In this regard, after the rapid rise in the popularity of information technologies, there is a slight decline in popularity, but they remain in the top of popular trends. Since the start of the COVID-19 pandemic, funding in the fitness and wellness industry has grown significantly, with an average of $11.9 million raised annually starting in 2021 (and including early 2023). As wave after wave of COVID variants hit the world, people were forced to stay at home and find new ways to stay active and healthy. As a result, many new companies have entered the fitness and wellness space, with a large number of them raising money in private online marketplaces. In general, among the most popular directions are the following: online fitness plans; fitness equipment for the home; portable media; virtual reality; exercise machines and recovery tracking programs; Artificial Intelligence; applications for combining physical and mental health (wellness technology). In recent years, the world has seen an increase in the number of users of applications related to the recreation and health industry. According to data, in 2015 the number of users of such applications was 150 million, and already in 2021 this number has increased to 385 million. Ukrainian users are also actively involved in these technologies, which is reflected in the popularity of applications.
Keywords: modern technologies; fitness; innovations; trends; application; physical activity